Grand excursions on the upper Mississippi River : places, landscapes, and regional identity after 1854 - Roseman, Curtis C.; Roseman, Elizabeth M. (Elizabeth Mercer), 1948- (Bur oak book., 2004)
N June 1854 the Grand Excursion celebrated in festive style the completion of the Chicago and Rock Island Railroad to the Mississippi River. Hundreds of dignitaries including newspaper editors and other journalists; politicians; academics, writers and artists; business and industry leaders; and railroad officials were among those who traveled by rail from Chicago to Rock Island, Illinois, then by steamboat to St. Paul in Minnesota Territory. The travelers were shown a region undergoing rapid settlement by Europeans-an area of great natural beauty offering many promises for additional developme.